GEOPOETICS IN «THE HEART OF PARMA» BY ALEXSEY IVANOV - I. N. Ivanova; A. S. Sazonova (Гуманитарные и юридические исследования)
The article is devoted to the current direction in literary criticism - geopoetics. Geopoetics as a scientific method allows us to analyze a work of art as a system of geopoetic images and symbols. This article examines the phenomenon of the Ural text in the novel by A. Ivanov «The Heart of Parma, or Cherdyn is the Princess of the mountains». Within this approach, first of all, we consider the cultural and geographical space of the Urals and its interaction with the characters of the work. The work by A. Ivanov is not studied in isolation, but in the context of the previous prose about the Urals. The main sources are the tales of P.P. Bazhova and «The Word of the Life and Teaching of the Holy Father of Our Stephen, Bishop of Perm» Epiphanius the Wise. Thanks to this, it be comes possible to isolate the structural elements of the Urals text. In the article, the main typological features of the Uralic text are singled out: the deification of nature, the motive for testing the character with a mysterious mystical force, the motives for destiny, milestones, conquest and development of the Urals, images of land, animal images (swan, falcon, etc.), stone mountains and rivers, the image of the system of oppositions (center/boundary, terrestrial/heavenly, good /evil, one's own/alien), the opposition of Russian and Ural cultures, the cult of chthonic deities that personify the wild nature of the Urals.